URBAN MUSLIMS IN HIGHER EDUCATION: CAMPUS DA’WAH ACTIVISTS’ MASTER NARRATIVES ON POLYGAMY VIEWS - Dian Furqoni Tenrilawa; Zezen Zainul Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
This research will examines the polygamy narratives of Campus Da'wah Activists during the rise of polygamy discourse in Indonesia. Campus Da'wah activists are part of the urban Muslims who have intellectual and social duties to preach religion within the scope of the campus level. This research is field research with the object of research being Campus Da'wah Activists on three major campuses in Yogyakarta, the research uses Master Narrative theory as a dissection of the narrative used. The findings in the study show that there are three groups of views on polygamy, namely pro-polygamy, conditional pro-polygamy, and counter-polygamy, while the main narratives that develop, the pro-polygamy group views the inequality of the ratio of men and women as unbalanced, the conditional pro-polygamy group emulates the story of Siti Sarah who is willing to be polygamous in an emergency, while the counter-polygamy group makes the love story of the Prophet Muhammad with Siti Khadijah which teaches marital fidelity. This research is expected to contribute to the narrative that is developing in the community towards polygamy, which is not only based on lust but also the guidance of Shari'a.